18x +12y = 0
It's a linear expression in two unknowns.It can be simplified a little bit:18x + 14y + 3x - 10y = 21x + 4y
It can be simplified to: 2x+86
x2 + 18x = x(x + 18) which cannot be simplified further.
(2x4) + (8x3) + 18x 8 + 24 + 18x 32 + 18x
The equation 6 x-1 18x can be simplified to the answer 112x.
If you mean (11x -8)+7(x -1) then it is 18x -15 when simplified
18x + 45 or 9(2x + 5) how is this answer figured?
x2 + 18x - 50 does not have rational factors.
18x + 24 6(3x + 4) is factored fully
It is: 0
9x2 - 18x + 99(x2 - 2x + 1)==========
6x2-18x+12 = (6x-6)(x-2)
5x2-18x+9 = (5x-3)(x-3)
7Improved Answer:8x2-18x+9 = (4x-3)(2x-3)
Add them together and so -16x+2+18x becomes 2x+2
The vertex is (-9, -62).
18x + 5
49/122 is in its simplest form.
9(2x + 5)
It is 0.